Investigation of Changes in Dental Pulp Tissue in Rats with Bilateral Ovariectomy by Histopathological Methods - Bakir, Elif Pinar; Bakir, Şeyhmus; Deveci, Büşra; Şahin, Firat; Aşir, Firat; Deveci, Engin (The Journal of Dentists, 2021)
In this study, we aimed to investigate the histopathological changes on 14th and 28th days in the dental pulp of ovariectomized rats. Twenty 12-week-old 21 female Sprague Dawleys were divided into 3 groups. Group 1: No procedure was applied to the animals. All teeth were excised at the end of the experiment (at the 14th day of experiment). Group 2: The abdomen was opened and the ovary tied with 3/0 silk sutures to block blood supply. The ovaries were placed in its original position. Teeth of ovariectomized rats were excised at the 14th day of experiment. Group 3: Similar procedure was applied as in Group 2. The teeth were removed on 28th days of experiment. The dental tissues taken after the experiment were processed for routine paraffin wax tissue preparation. Hematoxylin-Eosin staining was applied to sections of 4 μm thickness. As a result, when compared to the dental pulp of control group, degenerated dental pulp tissue, vascular dilatation and pyknotic osteoblast cells were observed in ovariectomized rats, however the pathological intesity was higher in ovariectomized rats for 28 days than ovariectomized rats for 14 days.